The Effect of a Continuous Nursing Care Program on the Quality of Life of Toddlers with Pneumonia, Parental Stress Levels, and Parental Satisfaction - Rosuliana, Novi Enis; Mawaddah, Ely; Kusmiyati; Nurhayati, Tetik; Ningsih, Mira Utami; Happy Bandana Biswas (Jurnal Kesehatan Prima, 2025)
Pneumonia is an acute infectious disease that occurs in toddlers caused by bacteria, viruses, and fungi. Risk factors for pneumonia are prematurity, BBLR, lack of exclusive breast milk, cigarette smoke, air pollution and congenital heart defects. The death rate of children under five in the world due to pneumonia in 2019 began to decline but the decline was lower than other infectious diseases. Data shows that pneumonia and diarrhea cause 2 million children to die each year. Toddler pneumonia in Indonesia is the second leading cause of death, with a mortality rate of 0.16% for toddlers, while West Java is among the 10 provinces with the most pneumonia cases, and Tasikmalaya Regency is among the 10 most regions with 1,814 cases of toddler pneumonia. Based on these data, appropriate management is needed to reduce the morbidity and mortality of pneumonia in toddlers. The research method is a quasi-experimental design of a pre-test post test with a control group design. The population of all hospitalized toddlers, the number of 30 respondents for the intervention group and the control group used time-based accidental sampling. Data analysis was univariate and bivariate analysis using the Wilcoxon Signed Ranks Test and the Mann Whitney-U test. The research instrument used questionnaires, namely demographic data, Perceived Disease Severity Scale, childcare stress questionnaire, child quality of life questionnaire (PedsQLTM 4.0), and satisfaction questionnaire. The results showed that the interventions given in the intervention group showed that there was an effect of the Continuing Nursing Care Program on quality of life p-value 0.007, nursing stress (p-value 0.006), and hospitalization satisfaction (p-value 0.011), as well as inpatient satisfaction in the control group (p-value 0.044). This shows that the Continuing Nursing Care Program is effective in providing nursing care for toddlers with pneumonia in hospitals.